(3QSGdI aj Yde GdcdGes
(3ChdgG (B:s
(3CYde Cf GdajGV ggfG efbhd ZjQ eYfGg GddZhi hgh GdcKjQ cKQI eNUhUI HGdeGA Edi GdeGA s
(3BNQgG (B:s
(3hGdcdGe ggfG ai Jdc GdZGjg dG ai GdChd aEfgG ai Gdcd TF hGMO gh GdeHOF GdChd JYGdi TCfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs